Dynamic imaging of cytosolic zinc in Arabidopsis roots combining FRET sensors and RootChip technology - Lanquar, Viviane; Großmann, Guido (The new phytologist, 2013)
* Zinc plays a central role in all living cells as a cofactor for enzymes and as a structural element enabling the adequate folding of proteins. In eukaryotic cells, metals are highly compartmentalized and chelated. Although essential to characterize the mechanisms of Zn2+ homeostasis, the measurement of free metal concentrations in living cells has proved challenging and the dynamics are difficult to determine. * Our work combines the use of genetically encoded Förster resonance energy transfer (FRET) sensors and a novel microfluidic technology, the RootChip, to monitor the dynamics of cytosolic Zn2+ concentrations in Arabidopsis root cells. * Our experiments provide estimates of cytosolic free Zn2+ concentrations in Arabidopsis root cells grown under sufficient (0.4 nM) and excess (2 nM) Zn2+ supply. In addition, monitoring the dynamics of cytosolic [Zn2+] in response to external supply suggests the involvement of high- and low-affinity uptake systems as well as release from internal stores. * In this study, we demonstrate that the combination of genetically encoded FRET sensors and microfluidics provides an attractive tool to monitor the dynamics of cellular metal ion concentrations over a wide concentration range in root cells.
Gesehen am 22.05.2017